2021
DOI: 10.1111/1467-9604.12339
|View full text |Cite
|
Sign up to set email alerts
|

Think piece on parents, ‘off rolling’ and wavelength methodology: issues for SENCos

Abstract: This think piece argues for a novel qualitative methodology that permits social justice researchers, including National Award for Special Educational Needs Coordination students, to highlight the profound affects of exclusionary school practices for parents of children with SEN and/or disabilities (SEND). Such children are proportionately effected by these practices. The piece was prompted by multi-strand research into 'off rolling' (illegal exclusionary practices), in which 53 parents described the process th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Nevertheless, the insights gained into SENCos' work during this time can inform future research design. The illegality of some exclusionary practices has previously raised concerns about the authenticity of participant responses and levels of understanding of what constitutes an illegal exclusion (Done & Knowler, 2021 ; Done et al, 2021 ), and similar concerns arose in the reported study.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Nevertheless, the insights gained into SENCos' work during this time can inform future research design. The illegality of some exclusionary practices has previously raised concerns about the authenticity of participant responses and levels of understanding of what constitutes an illegal exclusion (Done & Knowler, 2021 ; Done et al, 2021 ), and similar concerns arose in the reported study.…”
Section: Introductionsupporting
confidence: 55%
“…The Covid‐19 pandemic has both highlighted and exacerbated familiar issues related to SEND provision in English schools, including the apparent reluctance of an as‐yet unknown proportion of SENCos to challenge exclusionary practices and inconsistencies related to inclusive practice (Done et al, 2021 ). The post‐pandemic period presents an opportunity to review educational priorities thoroughly in relation to students with SEND and marginalised social groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaining insight into the divergent viewpoints in these groups is integral to poststructuralist analysis of relations of force that expand or limit agentic possibilities. The characterisation of this multi‐stranded and evolving research project as deploying a ‘wavelength methodology’ (Done et al., 2021) is apt since it is the amplitude of wavelengths which determines volume and, accordingly, only purposeful listening will ensure the audibility of some wavelengths. Similarly, the electromagnetic spectrum contains visible light but also invisible components such as radio waves and microwaves; the latter may not be visible but can be detected and their effects made visible.…”
Section: Methodsmentioning
confidence: 99%
“…There were only 21 responses to the senior leader survey, all from urban secondary settings, with a small proportion that had training in SEN provision coordination (SENCos). Consequently, the research then evolved into a multi‐stranded project, including data collection from parents (Done et al., 2021) and SENCos and the analysis of social media posts from education professionals.…”
Section: Researching ‘Off‐rolling’mentioning
confidence: 99%